Patient-specific phantoms versus reference phantoms: a preliminary comparison on organs dose distribution (Brazilian Journal of Radiation Sciences (BJRS), 2018)
Discrepancies between ICRP phantoms and real patients lead to disparities on patient-dose estimations. This paper aims to compare distribution of dose in organs of male/female individualized-phantoms and ICRP reference phantoms. The absorbed dose estimation was performed using the EGSnrc Monte Carlo code and a parallel source algorithm. In this work were used an individualized-phantom for a man (1.73m/70.3kg) and another for a woman (1.63m/60.3kg) and the male and female ICRP reference phantoms. The comparison of the absorbed dose from each phantom gender was performed using the relative error. The results were expressed in terms of conversion coefficients to brain, lungs, liver and kidneys. The greatest absolute relative error between the organs of the patient-specific and the reference phantom was 22.92% in the liver and 62.84% in the kidneys, respectively for man and woman. There are errors that cannot be disregarded. This paper shows the need for a specific study for each patient or for the population of each country, since there are different body types, which affects the distribution of the organ doses.